Deviated nasal septum in children: a review - Swain, Santosh Kumar (International Journal of Contemporary Pediatrics, 2022)
Deviated nasal septum (DNS) is a common clinical entity in human beings. Deviated nasal septum (DNS) may also result in upper respiratory infection, sinusitis, headache, epistaxis, middle ear infection, and hyposmia which increase the morbidity of the child and hamper the quality of life. The common clinical symptoms associated with DNS among children are nasal obstruction and postnasal discharge. The chronic nasal block in DNS has an adverse effect on the development of the child. DNS has an important effect on the faciomaxillary growth and development, particularly in the first decade of life. The treatment of DNS in childhood has received challenges among otolaryngologists because of its concern about the role of the nasal septum in the overall growth of the midface. So, otolaryngologists are often cautious during the correction of the DNS in children. DNS and its impact on nasal breathing impairment in children are often underestimated by clinicians. Clinicians often have little knowledge on the impact of DNS, its clinical manifestations in children, and its appropriate management. Early intervention for DNS in children is helpful to prevent morbid symptoms and their complications. This review article discusses etiopathology, epidemiology, clinical presentations, diagnosis, and current treatment of the DNS in children.